2021
DOI: 10.7759/cureus.20483
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Probiotics in the Management of Helicobacter Pylori: A Systematic Review

Abstract: Helicobacter pylori is a Gram-negative microorganism that causes chronic dyspepsia, gastritis, mucosa-associated lymphoid tissue (MALT) lymphoma, and gastric adenocarcinoma. Various antibiotic regimens are employed to eradicate it; however, antibiotic resistance has skyrocketed in recent years, resulting in a reduction in eradication rates. As a result, numerous novel therapeutic approaches are being adopted in clinical practice, and probiotics are being extensively investigated. Probiotics are livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…Patient education had positive effects on the H. pylori eradication rate and medication adherence [45]. Probiotics, in conjunction with recommended therapies, slightly increased the eradication rate and significantly decreased the adverse effects of antibiotics [46]. Susceptibility testing may guide the selection of the most effective treatment regimens and improve the eradication rate to exceed 90% [47].…”
Section: Discussionmentioning
confidence: 99%
“…Patient education had positive effects on the H. pylori eradication rate and medication adherence [45]. Probiotics, in conjunction with recommended therapies, slightly increased the eradication rate and significantly decreased the adverse effects of antibiotics [46]. Susceptibility testing may guide the selection of the most effective treatment regimens and improve the eradication rate to exceed 90% [47].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have confirmed that probiotics in conjunction with standard therapies have a beneficial effect on these complications and help to improve patient compliance to the routine treatments. 16,39 Another important point is the lack of a significant ameliorating effect of probiotics alone on H. pylori eradication. 39 In conclusion, combination of probiotics with traditional therapies can be considered as a novel therapeutic approach for H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…16,39 Another important point is the lack of a significant ameliorating effect of probiotics alone on H. pylori eradication. 39 In conclusion, combination of probiotics with traditional therapies can be considered as a novel therapeutic approach for H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses show that probiotic monotherapy has a minimal impact on the eradication rates of H. pylori. However, when used in supplementary therapy, probiotics are effective in increasing eradication rates with reduced side effects (Losurdo et al, 2018;Zhou et al, 2019;Zhang et al, 2020;Penumetcha et al, 2021). The Maastricht VI/Florence consensus report also states that probiotics can increase the eradication rate of H. pylori by reducing side effects associated with eradication therapy rather than through direct effects on H. pylori, but the benefit only apply to certain strains of probiotics (Malfertheiner et al, 2022).…”
Section: Probiotics Therapymentioning
confidence: 99%